Aqueous Extract of (Eruca sativa Mill) as Growth Stimulant in Enhancing Growth and Yield of Faba Bean (Vicia faba L) - Ehtaiwwesh, Amal F; Qarimidah, Fouziyah (Al-Mukhtar Journal of Sciences, 2021)
A field study was conducted in the fall of 2019 to investigate the potential of Arugula (Eruca sativa Mill) aqueous extract as a growth stimulant in enhancing the growth and yield of Fa- ba Bean (Vicia faba L). The study was conducted using sandy soil at a farm in Abo Esaa town in a plot size of 3X5 m2 with a row spacing of 25cm,which based on a complete randomized design (RCD) with four replications, three treatments were carried out, including no foliar spray with E. sativa extracts (control) and foliar sprayed with 20% and 40% aqueous extracts of E. sativa. Ac- cordingly, Faba Bean (Vicia faba L) plants were foliar sprayed six times with the aqueous extracts of E. sativa at rates of 20 and 40% at vegetative and reproductive stages. The result showed that among these concentrations, the foliar spray of faba bean plants with 40% of E. sativa extracts po- tentially were increased all measured growth and yield traits. The results pointed out that plant height increased by 32%, number of branches by 73%, number of leaves by 95%, number of seeds plant by 89%, leaves, stems, pods and roots dry weight by 92%, 80%, 74%, and 89%, respectively. Thus, the study concluded that E. sativa aqueous extracts could potentially be used efficiently by crop producers as a growth enhancer for faba bean crops because of their productivity, great nutri- tive value, low cost, and environmentally friendly nature.